Vocademy: A Mobile Learning Application to Enhance Vocational Students’ Critical Reading Skills in English for Engineering - Santi Kusuma Dewi; Mustaji; Andi Mariono (Poltanesa, 2025)
This study aimed to develop and evaluate Vocational English Academy (Vocademy), a specialized mobile learning application designed to significantly enhance the critical reading skills of vocational students in the context of English for Engineering at SMKN 1 Nganjuk. We employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) coupled with a mixed-method approach, integrating a quasi-experimental one-group pretest-posttest design with descriptive qualitative analysis. The research participants comprised 72 tenth-grade students, evenly selected from the Geomatics and Mechanical Engineering programs based on their needs and accessibility. Data collection relied on comprehensive instruments, including expert validation sheets, a robust critical reading assessment (pre-test and post-test), and a student feedback survey. The development phase confirmed Vocademy’s quality; expert validation results showed exceptionally high validity and feasibility, boasting an average score of 89%. Following the intervention, quantitative analysis using a paired-sample t-test revealed a statistically significant improvement in students' critical reading skills (p < 0.05). The magnitude of this improvement was quantified by an N-Gain value of 0.464 (Medium Category), indicating strong instructional effectiveness. In conclusion, Vocademy has successfully proven its capability to elevate vocational English language education by effectively fostering high-level critical analysis and contextual comprehension of intricate technical documents. This positions the application as a highly relevant and innovative digital platform, essential for preparing graduates to meet the complex literacy demands of the Industry 5.0 era.